Bede and Aethelthryth - Harris, Stephen J.,Beda (West Virginia University Press, 2016)
This book attempts to reconstruct the horizon of expectation of a highly learned, Latin-speaking nun as she encounters a 50-line poem by the Venerable Bede, the Hymn to Aethelthryth – Note on orthography – On beauty – Metrical arts – Rhetoric – Sources – St. Aethelthryth in the HE [Historia Ecclesiastica] – Hymn to Aethelthryth (English) – Hymn to Aethelthryth (Latin) – Hymn to Aethelthryth (Edition) – Hymn to Aethelthryth, a-g – Hymn to Aethelthryth, h-r – Hymn to Aethelthryth, s-end
Includes bibliographical references and index
Keywords: Bede; Historia ecclesiastica gentis Anglorum; Christian poetry; Latin